(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The globalization of modern society makes certain adjustments already in the process of preparing for the lesson, which consist in the need to use mass media, which is dictated by the speed of information transmission in modern society. In this article highlights of effective use of modern educational equipment and tools in the integration of subjects in primary education.